Scaffold 3D‐Printed from Metallic Nanoparticles‐Containing Ink Simultaneously Eradicates Tumor and Repairs Tumor‐Associated Bone Defects. Issue 9 (1st August 2021) - Lin, Huimin; Shi, Shanwei; Lan, Xinyue; Quan, Xiaolong; Xu, Qinqin; Yao, Guangyu; Liu, Jia; Shuai, Xintao; Wang, Chong; Li, Xiang; Yu, Meng
Abstract: Bone metastasis occurs in about 70% of breast cancer patients. The surgical resection of metastatic tumors often leads to bone erosion and destruction, which greatly hinders the treatment and prognosis of breast cancer patients with bone metastasis. Herein, a bifunctional scaffold 3D‐printed from nanoink is fabricated to simultaneously eliminate the tumor cells and repair the tumor‐associated bone defects. The metallic polydopamine (PDA) nanoparticles (FeMg‐NPs) may effectively load and sustainably release the metal ions Fe 3+ and Mg 2+ in situ. Fe 3+ exerts a chemodynamic therapy to synergize with the photothermal therapy induced by PDA with effective photothermal conversion under NIR laser, which efficiently eliminates the bone‐metastatic tumor. Meanwhile, the sustained release of osteoinductive Mg 2+ from the bony porous 3D scaffold enhances the new bone formation in the bone defects. Taken together, the implantation of scaffold (FeMg‐SC) 3D‐printed from the FeMg‐NPs‐containing nanoink provides a novel strategy to simultaneously eradicate bone‐metastatic tumor and repair the tumor‐associated bone defects. Abstract : A bifunctional 3D‐printed scaffold (FeMg‐SC) based on PDA nanoparticles containing Fe 3+ and Mg 2+ (FeMg‐NPs) is used to treat bone metastatic tumors and to realize subsequent bone repair. The scaffold released Fe 3+ in planted site to display a potent synergistic CDT/PTT for tumor cell kiliing, while releasing Mg 2+ to enhance osteoblastic differentiation for tumor‐associated bone defects repair.